SAT0318 Epigenetic regulation of FRA2 by JMJD3 regulates fibroblast activation in systemic sclerosis. (15th June 2017) - Bergmann, C; Brandt, A; Dees, C; Wohlfahrt, T; Zhang, Y; Chen, C-W; Mallano, T; Liang, R; Kagwiria, R; Kam, P-S; Bozec, A; Abraham, D; et al.
Abstract : Background: Chronic and exaggerated fibroblast activation is a central hallmark of Systemic Sclerosis (SSc) fibrotic disease and results in a high morbidity and mortality. Epigenetic changes might play important roles in mediating chronic fibroblast activation. Trimethylation of H3 at lysine residue K27 (H3K27me3) is a repressive epigenetic mark that was recently identified as an important negative regulator of fibroblast activation [1]. Jumonji domain containing protein 3 (JMJD3) mediates H3K27me3–demethylation. JMJD3 inhibitors are being tested as therapeutic strategies in malignant diseases. Objectives: The aim of this study was to characterize the role of JMJD3 in fibrotic disease and to explore JMJD3 as a potential drug target in SSc. Methods: Expression analyses of JMJD3 were performed using qPCR, IF and Western blot. siRNA mediated knockdown and the pharmacologic H3K27me3-demethylase inhibitor GSKJ4 were used to target JMJD3. In vivo, we analyzed the effects of GSKJ4 in bleomycin-induced dermal fibrosis and in Topoisomerase-I-induced (TopoI) fibrosis. H3K27me3 levels at the Fra2 promotor were analyzed by CHIP. Results: We observed increased expression of JMJD3 in SSc skin compared to healthy controls. Fibroblast-specific overexpression of JMJD3 was also reflected in experimental fibrosis models. TGFβ upregulated JMJD3. Inhibition of JMJD3 increased H3K27me3 in vitro and in vivo . Inhibition of JMJD3 reverted the activated fibroblast phenotype in SSc fibroblasts and decreased the expression of contractile fibers and of α-smooth muscle actin. In addition, JMJD3 inhibition reduced the basal and TGFβ induced collagen secretion of SSc fibroblasts. JMJD3 regulated the TGFβ induced expression of Fra2. GSKJ4 reverted the TGFβ induced reduction of H3K27me3 at the Fra2 promotor. Moreover, the anti-fibrotic effects of JMJD3 inhibition were evened in Fra2 knockout fibroblasts. Overexpression of Fra2 in JMJD3-knockdown fibroblasts restored the profibrotic effect of JMJD3. In vivo, inhibition of JMJD3 ameliorated fibrosis in bleomycin- and TopoI- induced experimental fibrosis and reduced dermal thickening, hydroxyproline content and myofibroblast differentiation. Conclusions: We present first evidence that JMJD3 contributes to the activated phenotype of SSc fibroblasts. TGFβ upregulated JMJD3. Inhibition of JMJD3 prevented the aberrant activation of fibroblasts in vitro and ameliorated dermal fibrosis in several mouse models in vivo . The profibrotic effects of JMJD3 might be mediated by reducing the H3K27me3 at the Fra2 promotor and consecutive overexpression of Fra2. References: Kramer, M., et al., Inhibition of H3K27 histone trimethylation activates fibroblasts and induces fibrosis. Ann Rheum Dis, 2013. 72(4): p. 614–20. Disclosure of Interest: None declared